Cost-effective carbon supported Fe2O3 nanoparticles as an efficient catalyst for non-aqueous lithium-oxygen batteries. (1st September 2016) - Wu, M.C.; Zhao, T.S.; Tan, P.; Jiang, H.R.; Zhu, X.B.
Abstract: In this work, we synthesize inexpensive Vulcan XC-72 carbon supported Fe2 O3 nanoparticles (Fe2 O3 /XC) as an oxygen evolution reaction (OER) catalyst for non-aqueous lithium-oxygen batteries. It is demonstrated that the battery with the Fe2 O3 /XC cathode exhibits a charge voltage plateau of 4.01 V at a current density of 200 mA g −1, which is 0.43 V lower than that with the pure XC carbon cathode. The battery also presents an outstanding rate capability, giving a charge voltage plateau of 3.99, 4.01 and 4.15 V at the current density of 100, 200 and 400 mA g −1, respectively. Furthermore, the battery can be operated for 50 cycles at a fixed capacity of 500 mA h g −1 without obvious degradation, showing its superior cycling stability. The results suggest that the iron oxide is a cost-effective catalyst for non-aqueous lithium-oxygen batteries.